Studi Eksperimental Campuran AC – WC Menggunakan Aspal Modifikasi Karet Alam Dengan Variasi Suhu Pemadatan Terhadap Nilai Durabilitas - Dhanil Ramadhan; Putri*, Lusi Dwi; Fitridawati Soehardi (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2024)
Changes in asphalt temperature can cause deformation damage and cracks in the asphalt so that the appropriate temperature is needed to prevent damage in the field. Durability is the resistance of asphalt to changes in temperature, weather, water and air, asphalt with poor durability will cause the asphalt surface to be easily damaged and the surface can deform so that the asphalt becomes bumpy and endangers driving activities, poor durability also results in reduced road plan life. This study aims to determine the durability value of natural rubber asphalt using compaction temperature variations of 100 ℃, 100 ℃, 110 ℃, 120 ℃, 130 ℃ and 140 ℃. The research started with the examination of aggregate properties and asphalt properties then continued with making test specimens to determine the optimum asphalt content with variations of 5%, 5.5%, 6%, 6.5%, 7% obtained optimum asphalt content of 6.38%. Next, make test specimens with variations in compaction temperature of 100 ℃, 110 ℃, 120 ℃, 130 ℃ and 140 ℃. After the specimens are made based on the compaction temperature variation, durability testing is carried out for 30 minutes and 24 hours in a waterbath tool using a temperature of 60 ℃. From this test, the durability value is obtained at 100 ° C durability value 116%, 110 ° C durability value 103%, 120 ° C durability value 93%, 130 ° C durability value 85%, 140 ° C durability value 80%. The results of the calculation of the durability value. The results of the calculation durability value at a compaction temperature of 100 ℃ to 120 ℃ meet the specifications of Bina Marga 2020 where the durability value is at least 90%, while at temperatures of 130 ℃ and 140 ℃ the durability value does not meet the specifications of Bina Marga 2020. The conclusion of this research is that durability decreases with increasing compaction temperature.